2020
DOI: 10.1007/s13670-020-00326-6
|View full text |Cite
|
Sign up to set email alerts
|

Home Exercise Interventions in Frail Older Adults

Abstract: Purpose of Review Frailty is characterized by decreased physiological reserve and increased risk of falls, disability, hospitalization, and mortality. Frail older adults may benefit from exercise interventions targeting their multiple problems and functional deficits; however, most research focuses on center-based interventions, which may present accessibility challenges for frail older adults. Therefore, the purpose of this review is to summarize the most recently published home-based exercise interventions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
(131 reference statements)
1
6
0
2
Order By: Relevance
“…There is an anticipated attrition rate with any study, not least studies involving an older, frail and multimorbid population [42]. Studies of home exercise interventions for older adults living with frailty have reported retention rates ranging from 53-98% [22]. In our study, decision to withdraw appeared to be influenced by perceived ineffectiveness and a fear of worsening symptom experience with physical activity.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…There is an anticipated attrition rate with any study, not least studies involving an older, frail and multimorbid population [42]. Studies of home exercise interventions for older adults living with frailty have reported retention rates ranging from 53-98% [22]. In our study, decision to withdraw appeared to be influenced by perceived ineffectiveness and a fear of worsening symptom experience with physical activity.…”
Section: Discussionmentioning
confidence: 69%
“…However, the authors acknowledged that the generalisability of findings is "limited by age" as the "approximate mean age of participates in the included trials ranged from 50 to 65 years" [21]. Studies in older frail non-CKD populations suggest that home-based exercise interventions are feasible and may be associated with improved outcomes, in terms of frailty, functional performance, nutritional status and falls incidence [22]. However, research is needed to evaluate home-based exercise interventions tailored to the needs of older people living with frailty and CKD [23].…”
Section: Introductionmentioning
confidence: 99%
“…level one or two bed occupancy postoperatively. Identifying pre-frail as well as frail patients may allow for pre-habilitation to reduce frailty status (Stookey, 2020 ). This in turn may reduce surgical risk and improve patient outcomes (Hanna, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the implementation of these community programs is highly recommended, and physical activity of all types and combinations as well as rehabilitation significantly reduce the number or prevalence of markers of frailty (25) , the truth is that most programs focus on group activities of physical exercise, cognitive training and even emotional management (8) rehabilitation programs that individually meet the specific needs of each frail elderly are scarce (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies highly recommend multicomponent exercise and gerontogeriatric rehabilitation for frailty in the elderly, especially during the pre-frail phase (8,(10)(11)(12) . However, through a review of the literature, it was found that there are few individualized rehabilitation programs developed in the community, especially in the home context with the elderly in situations of frailty, making it difficult to access and adhere to these programs (13) . Despite this, few studies show that interventions such as home visits and supervised home physical exercise in frail elderly improve functional capacity and decrease the number of falls (14)(15)(16) .…”
Section: Introductionmentioning
confidence: 99%